2010
DOI: 10.1074/jbc.m110.123786
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Lineage Kinase-3 Stabilizes and Functionally Cooperates with TRIBBLES-3 to Compromise Mitochondrial Integrity in Cytokine-induced Death of Pancreatic Beta Cells

Abstract: Mixed lineage kinases (MLKs) have been implicated in cytokine signaling as well as in cell death pathways. Our studies show that MLK3 is activated in leukocyte-infiltrated islets of nonobese diabetic mice and that MLK3 activation compromises mitochondrial integrity and induces apoptosis of beta cells. Using an ex vivo model of islet-splenocyte co-culture, we show that MLK3 mediates its effects via the pseudokinase TRB3, a mammalian homolog of Drosophila Tribbles. TRB3 expression strongly coincided with conform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 55 publications
1
62
0
Order By: Relevance
“…Insulin was also reported to induce apoptosis in glucosedeprived β cells (Guillen et al 2008) and potentiate the deleterious effects of H 2 O 2 on β cell survival (Sampson et al 2010). Of special interest in this regard is our finding that insulin increased the expression of iNos and Trb3, factors whose expression is known to be increased by cytokines in pancreatic β cells (Kanki et al 2009, Humphrey et al 2010, Kanwar 2010, Quintana-Lopez et al 2013. Trb3 was recently shown to mediate FFA-induced apoptosis in pancreatic β cells (Qin et al 2014).…”
Section: :3mentioning
confidence: 55%
See 1 more Smart Citation
“…Insulin was also reported to induce apoptosis in glucosedeprived β cells (Guillen et al 2008) and potentiate the deleterious effects of H 2 O 2 on β cell survival (Sampson et al 2010). Of special interest in this regard is our finding that insulin increased the expression of iNos and Trb3, factors whose expression is known to be increased by cytokines in pancreatic β cells (Kanki et al 2009, Humphrey et al 2010, Kanwar 2010, Quintana-Lopez et al 2013. Trb3 was recently shown to mediate FFA-induced apoptosis in pancreatic β cells (Qin et al 2014).…”
Section: :3mentioning
confidence: 55%
“…Among the candidate ER stress proteins that might be involved in insulin effects is Trb3, a downstream target of Atf4, which has been found to be increased by cytokines (Kanki et al 2009, Humphrey et al 2010, Kanwar 2010),…”
Section: Insulin Induces Changes In Expression Of Er Stress Genesmentioning
confidence: 99%
“…In the N-terminus, mutations fail to induce AML in a Hox9 coexpression assay, while mutations in the COP1 binding site bind but fail to degrade C/EBP and also compromise the leukemogenic activity of Trib1 and Trib2. The Trib MEK1 motif ILLHPWF is thought to mediate interactions with multiple MAPkinase kinases (MAPKKs), including (1) Trib3 binding MLK3 in pancreatic b-cells (Humphrey et al, 2010); (2) Trib2 binding and inactivation of MKK7 and MEK1, involved in Erk and Jnk signaling, respectively (Eder et al, 2008); and (3) Trib1 binding and enhancing phosphorylation of ERK1/2, important for its leukemogenic activity (Yokoyama et al, 2010). Interdependence of these domains is suggested by Trib1 mutants that lack the MEK1 binding motif and fail to degrade C/EBPa, suggesting the COP1 function of Tribs is dependent on activation of the MEK1/ERK pathway .…”
Section: Conserved Features Of Tribs: a Swiss Army Knife Of Cell Signmentioning
confidence: 99%
“…While knockdown suppresses the effect of GMCSF withdrawal, overexpression of Trib2 stimulates apoptosis by means of a caspase, not the proteosome (Lin et al, 2007). Trib3 also promotes apoptosis in macrophages (Shang et al, 2009), gliomas (Salazar et al, 2009), pancreatic b-cells (Humphrey et al, 2010), and chondrocytes (Cravero et al, 2009). …”
Section: Tribs Promote Apoptosismentioning
confidence: 99%
“…JNK activation has been clearly linked to mitochondrial stress and damage in multiple cell types, including the pancreatic beta cell (4 -6). We have reported that cytokine-induced MLK3-JNK pathway is instrumental in compromising mitochondrial integrity early in the apoptotic process, effectively reducing cellular defenses and increasing the potency of subsequent inflammatory events (6).…”
mentioning
confidence: 99%